Assessment of Nurses' Knowledge About Parkinson's Disease: Penilaian Pengetahuan Perawat Tentang Penyakit Parkinson - Afkar Fadhial Kareem (Academia Open, 2025)
Background: Nurses play a pivotal role in delivering comprehensive care aimed at enhancing the health and quality of life of individuals, families, and communities throughout the lifespan. Specific Background: The evolving sociocultural landscape has significantly influenced the roles and responsibilities of the nursing workforce. Knowledge Gap: Despite the increasing prevalence of neurodegenerative disorders, limited data exist regarding nurses’ knowledge of Parkinson’s disease, particularly in low-resource settings. Aims: This study aims to assess the level of knowledge about Parkinson’s disease among nurses in Al-Basrah Teaching Hospitals and examine the influence of demographic variables such as gender, age, education, workplace, and experience. Results: A descriptive cross-sectional study was conducted among 75 nurses from three teaching hospitals using a structured questionnaire. Findings revealed that most participants were aged 20–40 years, had less than 20 years of experience, and possessed a school or institute-level education. Notably, the majority demonstrated a poor understanding of Parkinson’s disease. Novelty: This study highlights critical knowledge deficiencies among nurses in a region where Parkinson’s-related care is becoming increasingly relevant. Implications: Addressing this gap through targeted education and training may enhance early detection, management, and patient outcomes in neurodegenerative diseases within clinical settings. Highlights: Nurses show low knowledge of Parkinson’s disease. Age and education affect knowledge levels. Training needed to improve clinical Parkinson’s care. Keywords: Parkinson’s disease, nurse knowledge, Al-Basrah hospitals, neurodegenerative care, healthcare education